(untitled) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2023)
This article discusses the general concept and features of selection achievements, the conditions for the legal protection of selection achievements, the starting point of the legal protection of selection achievements, the principles of legal protection of selection achievements, patenting of selection achievements, the theories of scientists about selection achievements and selection rights of foreign countries, their features.